2019
DOI: 10.1002/ijgo.12930
|View full text |Cite
|
Sign up to set email alerts
|

Determining the cause of stillbirth in Kumasi, Ghana

Abstract: Objective: To classify cause-of-death (COD) for stillbirths occurring in a major referral hospital in Kumasi, Ghana. Methods: In a retrospective review conducted between June 8, 2011, and June 12, 2012, detailed information was collected on all stillbirths delivered at Komfo Anokye Teaching Hospital in Kumasi, Ghana. Patient records were independently reviewed by investigators using the Perinatal Society of Australia and New Zealand's Perinatal Death Classification system to determine COD for each case.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…From the introduction above, it could be clearly seen that although globally the incidence and prevalence of pregnancy loss (stillbirth, miscarriage, and abortion) is low, the situation seems to be different on the side in developing countries, in sub-Saharan Africa and Ghana in particular. Most hospital-based studies on pregnancy loss experiences among women in Ghana have clearly shown that there is a high rate of pregnancy loss experience among women [20][21][22] .…”
Section: Institute Of Health Research (Ihr) University Of Health and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…From the introduction above, it could be clearly seen that although globally the incidence and prevalence of pregnancy loss (stillbirth, miscarriage, and abortion) is low, the situation seems to be different on the side in developing countries, in sub-Saharan Africa and Ghana in particular. Most hospital-based studies on pregnancy loss experiences among women in Ghana have clearly shown that there is a high rate of pregnancy loss experience among women [20][21][22] .…”
Section: Institute Of Health Research (Ihr) University Of Health and ...mentioning
confidence: 99%
“…A hospitalbased study found that 54.8% of stillborns were males and 45.2% were females. In addition, 55.9% of the stillbirths were macerated, and 44.1% were fresh stillbirths [20] . The same study found that low maternal educational level, low socioeconomic status, and late and irregular antenatal attendance were present in the majority of the mothers who had stillbirths.…”
Section: Institute Of Health Research (Ihr) University Of Health and ...mentioning
confidence: 99%
“…Various issues surround the recording and classification of induced abortions, miscarriages and stillbirths in most low and middle-income countries, including Ghana [14]. These include limited early evaluation and documentation of risk factors, limited early dating to prevent post-date miscarriages and stillbirths, a limited availability of diagnostic testing, a large proportion of deliveries occurring outside of health facilities, lack of early identification of fetal distress and prompt delivery of such foetuses [15] and incomplete health records.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the wide recognition that stillbirths, induced abortions and miscarriages are common adverse pregnancy outcomes in Ghana [14,16], it appears empirical data on their risk factors are scanty. The few studies that have been carried out have found socio-economic (level of education, place of residence, wealth status, media exposure), demographic (age, religious beliefs, occupation) and biological (parity) predictors of stillbirths, induced abortions and miscarriages in Ghana [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Although advances have been made in reducing child mortality in this region, the numbers and rates of stillbirths remain high. 1 , 2 , 3 The causes of stillbirth in this region, as in most low-income and middle-income countries (LMICs), are mostly identified with verbal autopsy or clinical determination. 4 , 5 , 6 Compared with other causes of death, an accurate cause cannot often be identified through verbal autopsy or clinical observation, and, in some settings, more than 75% of all stillbirths have unknown causes.…”
Section: Introductionmentioning
confidence: 99%